Effectiveness of General Practitioners’ Involvement in Adult Vaccination Practices: A Systematic Review and Meta-Analysis of International Evidence - Andrea Ceccarelli; Gabriele Munafò; Francesco Sintoni; Christian Cintori; Davide Gori; Marco Montalti (Vaccines)
Background: General practitioners (GPs) and primary care units collaborate with Prevention Departments (PDs) to improve immunization by participating in vaccination campaigns, sharing tools, and implementing educational programs to raise patient awareness. This review aimed to identify effective strategies for involving GPs in PD vaccination practices. Methods: A systematic review following PRISMA guidelines was conducted on MEDLINE, TripDatabase, ClinicalTrials, CINAHL, and Cochrane up to January 2024 to identify full-text studies in English evaluating the effectiveness of GP involvement. A meta-analysis was also performed. Results: Of 1018 records, 15 studies were included, with an intermediate quality assessment. Studies originated from the United States (n = 9), Europe (5), Singapore (1), and China (1). Eight studies investigated educational programs for GPs, while seven focused on organizational or technological interventions to enhance immunization practices. Twelve studies reported increased vaccine uptake after intervention. Vaccines addressed included influenza, SARS-CoV-2, pneumococcal, zoster, and trivalent (diphtheria, tetanus, pertussis). Interventions involving GPs in PD vaccination campaigns, focusing on organizational or technological strategies, demonstrated a significant increase in vaccine uptake (OR = 1.15; 95% CI: 1.03–1.27; p < 0.0001; I2 = 96%). Conclusions: GPs emerged as valuable allies for PDs due to their extensive territorial reach and trusted relationships with patients. Additionally, up-to-date organizational and technological tools could play a decisive role in increasing vaccine uptakes. This study, offering valuable insights into the effectiveness of GPs involvement, may be useful to implement similar intervention in different contexts.